Benefits and limitations of drug studies in temperament research: biochemical responses as indicators of temperament. (19th April 2018) - Netter, Petra
Abstract : This paper presents a discussion of principles and problems of neurotransmitter challenge tests using examples of experiments, most of which were performed in the author's laboratory. Drugs targeting synthesis, release, receptors or reuptake of dopamine, serotonin and noradrenergic transmitter (TM) systems were used for characterizing or discriminating certain temperament or personality traits and their sub-factors. Any personality or temperament trait is characterized by multiple TM responses, thus constellations of hormone responses to drugs acting on different TM systems or on different sources of TM activity were investigated within individuals in crossover designs. The major conclusions are: (i) intra-individual patterns of hormone responses to different TM-related drugs, or to agonists and antagonists, can help to discriminate subtypes of temperament dimensions, and (ii) the latency and shape of response curves may help specify processes of biological responses related to psychological dimensions and reveal common TM sensitivities in clusters of traits. TM sensitivity, defined by hormone responses, does not always correspond to accompanying behavioural indicators, but may provide more specific information on underlying mechanisms. Additional consideration of drug doses and experimental induction of stressors may serve to identify temperament-related susceptibilities to certain drugs. Limitations of the challenge approach and recommendations for future research are discussed. This article is part of the theme issue 'Diverse perspectives on diversity: multi-disciplinary approaches to taxonomies of individual differences'.